Evaluation of Automated Photogrammetry Products as an Alternative to Architectural Plans for Archaeological Facades Documentation - Case study: The Evangelical Church in Lattakia - الخليل عمر; علي احمد (Latakia University Journal -Engineering Sciences Series, 2022)
Several methods are available for documenting archaeological facades. The architectural plans resulting from the topographic survey are the most accurate of these methods, but they are expensive and require time and effort to be completed. There are other ways to document these interfaces, including generating rectified images, which is suitable for planimetric interfaces, and 3D laser scanning, characterized by its high accuracy but it suffers from the problem of high cost. This paper presents a methodology for evaluating the products of Structure from Motion (SfM) photogrammetry and determine whether they constitute an accurate alternative to traditional topographic surveying of archaeological facades in order to obtain complete facade documentation. This method was applied to the western facade of the Evangelical Church in Latakia. The images needed for the modeling were taken with a mobile phone built-in camera. The reference data used is a measured distance in the façade space to scale the resulted model. The results of research showed that the orthophoto provides a measurement accuracy similar to the accuracy of the measurement on the architectural plans, and that the photorealist model is an important document when documenting the facades. On the other hand, the research showed that the 3D dense point cloud provides a basis for obtaining vector plans whose accuracy is from the order of the accuracy of architectural plans.